Aspects of Linguistic Variation - Olmen, Daniël (Trends in Linguistics. Studies and Monographs [TiLSM], 2019)
This volume brings together papers on linguistic variation. It takes a broad perspective, covering not only crosslinguistic and diachronic but also intralinguistic and interspeaker variation, and examines phenomena ranging from negation and TAM over connectives and the lexicon to definite articles and comparative concepts in well- and lesser-known languages. The collection thus contributes to our understanding of variation in general.